Identifying and categorising published conference proceedings - De Silva, S.M.; Zainab, A.N. (1999)
Identifies and categorises nine types of published conference proceedings using a sample of 61 published proceedings obtained from the University of Malaya’s Library (UML) online catalogue. Published conference proceedings were categorised based on relevant Anglo-American Cataloguing Rules, Revised Second Edition (AACR2R) in deciding on the form of main entry headings, title, statement of responsibility and access points. Interviews with expert cataloguers were conducted to find out the degree of agreement between the bibliographic descriptions they have given to a sample of records representing the 9 types with those given by the Library of Congress or Uni-versity of Malaya's online public access catalogue. Experts' responses helped to iden-tify probable problem areas encountered by cataloguers when cataloguing published conference proceedings.